Behaviour based safety checklist based on BOWEC requirements in construction industry (landed housing) - Sharifah Nurul Haifa, Syed Mohd Annuar (2019)
In the construction industry (landed housing), most of accidents and near-miss injury occur due to unsafe behaviour of the employers and employees in construction sites (landed housing). Lack of compliance with regulations is also one of the causes of accidents and near-miss injury occur in the construction industry (landed housing). This paper aims to identify Building Operations and Works of Engineering Construction (BOWEC) requirements and develop Behaviour-Based Safety (BBS) checklist based on BOWEC requirements in construction industry (landed housing). This paper also aims to validate BBS checklist by using case studies in construction industry (landed housing). A Microsoft Word and Microsoft Access are used in study to develop a system for BBS checklist. The concept used to develop BBS checklist is the Plan-Do-Check Act (PDCA). The BBS checklist was developed is divided into two parts, which are BBS checklist for employer and employees. The location of this study is at Kuantan, Pahang. For the data collection, BBS checklist which is in the system is used and the data was analysed by using percentage method. The percentage method is used to calculate the percentage of compliance with BOWEC requirements. The result shown, as of employer’s and employee’s BBS checklist overall complied with BOWEC requirements, is 82% and 77%. It was shown that more than half complied with BOWEC requirements. This study concludes with the result of the objectives. This shows that the company that have been chosen is the company that complies with the standards of Act and Regulation.